CORPORATE SOCIAL RESPONSIBILITY AND PROFITABILITY IN CIGARETTE SUB-SECTOR COMPANIES REGISTERED ON BEI IN 2012-2021 - Widy Nabila Safitri; Afrizawati Afrizawati; Keti Purnamasari (Jurnal Manajemen, 2024)
The purpose of this research is to determine the influence of Corporate Social Responsibility (CSR) and profitability on firm value. Profitability is assessed using Return On Assets (ROA) and Return On Equity (ROE), Corporate Social Responsibility (CSR) is measured using GRI G4 with 91 disclosure category indicators while firm value is measured using Price Book Value (PBV). The purposive sampling method was used to collect samples from companies in the cigarette sub-sector listed on the Indonesia Stock Exchange from 2012 to 2021. Classical assumption tests, multiple linear regression analysis, and hypothesis testing with the t test, f test, and coefficient of determination test were used. for data analysis in this research. The results of this research indicate that Corporate Social Responsibility has no influence on Firm Value. Return on Assets has a significant positive influence on firm value. Return on Equity has a significant positive influence on firm value. Corporate Social Responsibility, Return on Assets, and Return on Equity simultaneously influence firm value. Profitability as measured by Return on Assets has a dominant influence on firm value.